Active‐Site Imprinting: Preparation of Fe–N–C Catalysts from Zinc Ion–Templated Ionothermal Nitrogen‐Doped Carbons. Issue 43 (25th September 2019) - Menga, Davide; Ruiz‐Zepeda, Francisco; Moriau, Léonard; Šala, Martin; Wagner, Friedrich; Koyutürk, Burak; Bele, Marjan; Petek, Urša; Hodnik, Nejc; Gaberšček, Miran; Fellinger, Tim‐Patrick
Abstract: Atomically dispersed Fe–N–C catalysts are considered the most promising precious‐metal‐free alternative to state‐of‐the‐art Pt‐based oxygen reduction electrocatalysts for proton‐exchange membrane fuel cells. The exceptional progress in the field of research in the last ≈30 years is currently limited by the moderate active site density that can be obtained. Behind this stands the dilemma of metastability of the desired FeN4 sites at the high temperatures that are believed to be a requirement for their formation. It is herein shown that Zn 2+ ions can be utilized in the novel concept of active‐site imprinting based on a pyrolytic template ion reaction throughout the formation of nitrogen‐doped carbons. As obtained atomically dispersed Zn–N–Cs comprising ZnN4 sites as well as metal‐free N4 sites can be utilized for the coordination of Fe 2+ and Fe 3+ ions to form atomically dispersed Fe–N–C with Fe loadings as high as 3.12 wt%. The Fe–N–Cs are active electocatalysts for the oxygen reduction reaction in acidic media with an onset potential of E 0 = 0.85 V versus RHE in 0.1 m HClO4 . Identical location atomic resolution transmission electron microscopy imaging, as well as in situ electrochemical flow cell coupled to inductively coupled plasma mass spectrometry measurements, is employed to directly prove the concept of the active‐site imprinting approach. Abstract : The dilemma of the pyrolytic preparation of Fe–N–C catalysts lies in the metastability of active FeN4 sites at their formation temperature. Herein, the N4 motif of ZnN4 sites in atomically dispersed Zn–N–C substrates is successfully utilized for the low‐temperature preparation of active Fe–N–C catalysts with ion‐exchange reactions involving Fe 2+ or Fe 3+ ions.